Simple Percussion Ensemble on Early Childhood Social Development - Indra Yeni; Yul Syofriend; Sri Hartati; Vivi Anggraini; Desyandri; Alrizka Dilfa Hairi (Universitas Pendidikan Ganesha, 2023)
Early childhood is very fond of play activities. Based on observations in kindergarten group B, it was seen that 85% of children were not able to interact with friends and even teachers. This will have an impact on early childhood social development. The study aimed to analyze the use of percussion bottles filled with water on social development in children. This type of research is quantitative research. The research method uses a quantitative approach in the form of experimental quasi. The method used in collecting data is a test with early childhood research subjects. The instrument used in collecting data is the test question sheet. The technique used in analyzing data is inferential statistical analysis (t-test). The results of the study werethat children in the experimental class who used percussion bottles filled with water had a higher average score when compared to children in the control class who used applause. It was concluded that percussion bottles filled with water are effectively used to develop social development in early childhood. Simple percussion ensembles can help improve the pleasant learning atmosphere in students so as to improve social development in children.